2010
DOI: 10.1007/s10493-010-9388-2
|View full text |Cite
|
Sign up to set email alerts
|

Secretory process of salivary glands of female Amblyomma cajennense (Acari: Ixodidae) ticks fed on resistant rabbits

Abstract: Ticks have great economic and health importance since infested animals have reduced milk and meat production, and, besides that, they are expensive ectoparasites to control. While feeding, ticks can transmit to their hosts a large amount of pathogens, including Rickettsia rickettsii responsible for the "spotted fever" or "fever of the mountains." It is known that animals infested with ticks or artificially immunized with their salivary gland extracts develop resistance, which is related to a decrease in engorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
(21 reference statements)
2
8
0
Order By: Relevance
“…It is clear that the resistance of the host influenced in the secretory cycle of the infesting females glands, acting both in the secretory activity of the glandular cells (making them inactive) and leading the glands to early degeneration. Nunes et al (2010) and Jittapalapong et al (2008) have reported that the resistance acquired by the hosts studied by them induced the salivary glands of Amblyomma cajennense and R. (Boophilus) microplus females, respectively, to necrosis. On the other hand, the present study showed that the resistance of the host led to the loss of function (inactivity) of some secretory cells as well as to the early degeneration of the salivary glands due to the occurrence of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is clear that the resistance of the host influenced in the secretory cycle of the infesting females glands, acting both in the secretory activity of the glandular cells (making them inactive) and leading the glands to early degeneration. Nunes et al (2010) and Jittapalapong et al (2008) have reported that the resistance acquired by the hosts studied by them induced the salivary glands of Amblyomma cajennense and R. (Boophilus) microplus females, respectively, to necrosis. On the other hand, the present study showed that the resistance of the host led to the loss of function (inactivity) of some secretory cells as well as to the early degeneration of the salivary glands due to the occurrence of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the present study showed that the resistance of the host led to the loss of function (inactivity) of some secretory cells as well as to the early degeneration of the salivary glands due to the occurrence of apoptosis. However, it is known that different species of ticks respond differently to the resistance acquired by the host (Nunes et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations